2021
DOI: 10.1097/j.pain.0000000000002305
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal interaction between depression and pain: results from a comprehensive bidirectional Mendelian randomization study and functional annotation analysis

Abstract: Supplemental Digital Content is Available in the Text. Mendelian randomization study supports that depression is a causal risk factor for headache and pain at neck/shoulder, back, and abdominal/stomach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 40 publications
9
24
0
Order By: Relevance
“…Conversely, chronic facial pain increased the risk of seeking care for depression (i.e., pain → depression only [Supplementary Table S7]). These findings are broadly consistent with other genetic studies concerning depression and chronic pain, which have shown genetic causal relationships between chronic pain and depression, spanning both depression → pain pathways 5458 and pain → depression pathways. 20,52,55,59 Taken together, our results and previous findings 19,20,27,54,55 raise further intriguing hypotheses, such as that either or both causal directions may exist on a patient sub-group basis.…”
Section: Discussionsupporting
confidence: 91%
“…Conversely, chronic facial pain increased the risk of seeking care for depression (i.e., pain → depression only [Supplementary Table S7]). These findings are broadly consistent with other genetic studies concerning depression and chronic pain, which have shown genetic causal relationships between chronic pain and depression, spanning both depression → pain pathways 5458 and pain → depression pathways. 20,52,55,59 Taken together, our results and previous findings 19,20,27,54,55 raise further intriguing hypotheses, such as that either or both causal directions may exist on a patient sub-group basis.…”
Section: Discussionsupporting
confidence: 91%
“…Our finding that elevated depressive symptoms were associated with pain is consistent with recent literature, but provides an important extension to a middle‐income country 4,5,39,40 . We found evidence of an association between pain and incident elevated depressive symptoms, supporting a bidirectional association of both pain and depression across different study populations 4–6,23,39–42 . Although health factors were fairly consistent by gender, age, and social support differentially impacted pain, suggesting demographic and psychosocial factors may be major drivers of the gender differences observed in pain burden.…”
Section: Discussionsupporting
confidence: 89%
“…Shared risk factors included older age, lower educational attainment, comorbidities, and disability status. This is consistent with a recent Mendelian randomization study which leveraged genetic variants to establish a causal link between depression and pain at specific body sites 23 . More broadly, a literature review cross‐sectionally estimated a 65% mean prevalence of pain symptoms (i.e., self‐reported complaints of pain, chronic pain, or pain scales) in adults with depression in psychiatric and clinical settings.…”
Section: Introductionsupporting
confidence: 84%
See 2 more Smart Citations